You Are Cordially Invited to … the Distanced Participation in a Royal Wedding - Hugoson, Marlene (Traditiones, 2012)
<span style="line-height: 115%; font-family: 'Helvetica','sans-serif'; font-size: 11pt; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-bidi-font-family: AGaramondPro-Italic; mso-ansi-language: SL; mso-fareast-language: EN-US; mso-bidi-language: AR-SA; mso-bidi-font-style: italic;">On 19 June 2010 Swedish Crown Princess Victoria married Mr Daniel Westling. The wedding was celebrated not only in the capital city of Stockholm, but also in the groom’s home village, where some 6,000 people assembled to watch and celebrate the wedding beneath a giant television screen placed in a country field. As examples of this type of distanced participation become more noticeable in the ritual year, the phenomenon becomes increasingly interesting to follow. This time the investigation leads to the small village of Ockelbo, Sweden, where the municipality organised a large-scale village feast and consciously rooted the performance in the rural identity of the area. <span style="line-height: 115%; font-family: 'Helvetica','sans-serif'; font-size: 11pt; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-bidi-font-family: AGaramondPro-Italic; mso-ansi-language: SL; mso-fareast-language: EN-US; mso-bidi-language: AR-SA; mso-bidi-font-style: italic;">*** <span style="line-height: 115%; font-family: 'Helvetica','sans-serif'; font-size: 11pt; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-bidi-font-family: AGaramondPro-Italic; mso-ansi-language: SL; mso-fareast-language: EN-US; mso-bidi-language: AR-SA; mso-bidi-font-style: italic;">19. junija 2010 se je švedska kronska princesa Viktorija poročila z Danielom Westlingom. Poroke niso praznovali le v švedski prestolnici Stockholmu, marveč tudi v ženinovi domači vasi, kjer se je okrog 6000 ljudi zbralo k ogledu in praznovanju poroke pred ogromnim televizijskim zaslonom, nameščenim na podeželskem polju. Ker so primeri tovrstne oddaljene udeležbe v okviru ritualnega leta vse pogostejši, je ta fenomen postal zanimivejši za opazovanje. Tokrat je preiskava vodila v malo vasico Ockelbo na Švedskem, kjer je mestna občina organizirala obsežno vaško praznovanje in zavestno utemeljila izvedbo v ruralni identiteti področja.